Language phenomena of tourism enterprises in Bali - Sang Ayu Putu Eny Parwati (English, 2018)
Heterogeneous regions create various linguistic phenomena, such as bilingualism, prioritizing high-achieving languages, decreasing loyalty to a language, and so on. Speakers who are loyal in various ways will maintain their language. The loyal attitude of language speakers depends on the authority of the language so that speakers are required to use the language positively, not least by the tourism service entrepreneurs in Bali. The phenomena of prioritizing the use of foreign languages in the international world of tourism cannot be avoided. However, loyal and positive attitudes toward Indonesian have been shown by most entrepreneurs in Bali, represented by entrepreneurs in Kuta and Ubud regions. The application of the questionnaire method and applying quantitative and qualitative approaches. This study is able to describe language attitudes, from loyalty, pride, to adherence to the language norms of tourism service entrepreneurs in the Province of Bali towards Indonesian. The results showed that the businessmen who were engaged in tourism services stated positively supporting the partitioning of the Indonesian language and prioritizing the use of Indonesian in their business environment. On loyalty to the Indonesian language, both entrepreneurs gave more SS and S statements than TS and STS. Meanwhile, in the statement of pride in the Indonesian language which contained five negative statements most of the respondents stated TS, while for positive statements most stated S. In the statement of adherence to the norms or rules contained in the use of the Indonesian language, most respondents stated TS against negative statements and most also stated S against positive statements. Furthermore, based on the statistical calculation of the data obtained the average values for positive statements were good and good enough for negative statements.